Does multitasking mediate the relationships between episodic memory, attention, executive functions and apathetic manifestations in traumatic brain injury?. Issue 1 (27th May 2016) - Arnould, Annabelle; Rochat, Lucien; Dromer, Emilie; Azouvi, Philippe; Van der Linden, Martial
Abstract : Apathy is frequently described in patients with traumatic brain injury (TBI); its negative consequences particularly affect functional independence. Among apathetic manifestations, lack of initiative and lack of interest have mainly been associated with cognitive impairments. However, few studies have been conducted to precisely identify the underlying cognitive processes. Our aims were (1) to determine the best predictor of apathy from among several cognitive processes, including episodic memory and attention/executive mechanisms and multitasking, and (2) to examine to what extent multitasking could mediate the relationships between specific cognitive processes and lack of initiative/interest. Seventy participants (34 patients with TBI matched with 36 control participants) were given a questionnaire to assess anxio‐depressive symptoms, four tasks to assess specific cognitive processes, and one task to assess real‐life multitasking. Participants' relatives completed an apathy questionnaire. Multitasking, as assessed by the number of goals not achieved, was the only significant predictor of apathetic manifestations. In addition, the mediation analyses revealed that multitasking performance mediated the relationships between verbal episodic memory and lack of initiative/interest, whereas executive and attentional functions were only indirectly related to lack of initiative/interest due to their significant impacts on multitasking. These results shed new light on the aetiology of apathetic manifestations in patients with TBI, indicating how specific cognitive deficits are expressed in real‐life multitasking, and consequently, how they may lead to the development and/or maintenance of apathetic manifestations.